2017
DOI: 10.17159/2519-0105/2017/v72no10a3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study investigating the presence of voids in bulk fill flowable composites

Abstract: Objective: To investigate the presence of voids in bulk fill flowable composites. Methods: This study investigated two well-known bulk-fill flowable composites, Smart Dentin Replacement (SDR) (Dentsply/Caulk, Milford, Germany) and Filtek bulk fill flowable (FBF) (3M ESPE, Minnesota, USA). Three ampules of each material were randomly selected. The ampules were subjected to 3D Micro-CT (General Electric Phoenix V|Tome|X L240) reconstruction in order to assess the presence of any voids within the ampules. results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, porosities can be minimized through vacuum loading of syringes and the use of light-cured materials that can be applied in one layer, i.e., bulk-fill materials. The latter provides better adaptation to the surrounding tissue and is less prone to operator-dependent failures [78]. Unfortunately, in such a protocol polymerization, shrinkage of the bulk-fill composite remains a problem [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…However, porosities can be minimized through vacuum loading of syringes and the use of light-cured materials that can be applied in one layer, i.e., bulk-fill materials. The latter provides better adaptation to the surrounding tissue and is less prone to operator-dependent failures [78]. Unfortunately, in such a protocol polymerization, shrinkage of the bulk-fill composite remains a problem [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed that bacteria accumulate in voids [ 30 ], and the SEM analysis of three-year-old resin restorations indicated a bacterial collection in the exposed surface pores of the restorations [ 15 ]. In addition to the intrinsic properties of the restorative material, surface roughness may also arise from the inadvertent incorporation of voids (porosities) during manufacture or by the clinician during restoration placement [ 31 , 32 ] due to the technique of condensing and smearing the material into the cavity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of porosities (voids) in CRs may arise from the manufacturing process or the application technique (i.e., condensing of the material into the cavity) [ 11 , 12 ] and could result in fractures of the restoration [ 13 ], microleakage and increased surface roughness [ 14 ]. Voids are commonly found along the junction between the CR layers when the incremental technique is applied [ 15 , 16 ]. Additionally, spherical and well-defined voids are also regularly found in materials extruded from the original syringes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been reported that the voids have been observed in bulk-fill and flowable composites ampules. The presence of voids in restoration can cause problems in the physical and mechanical properties of the restoration [ 58 ]. In the present study, an ultrasonic scaler was applied to evaluate the change in the void volume.…”
Section: Discussionmentioning
confidence: 99%